2016
DOI: 10.1371/journal.pone.0146747
|View full text |Cite
|
Sign up to set email alerts
|

Decompressive Hemicraniectomy in a South American Population – Morbidity and Outcomes Analysis

Abstract: BackgroundMalignant cerebral artery strokes have a poor prognosis, with nearly 80% of mortality in some series despite intensive care. After a large randomized trial, decompressive hemicraniectomy has been performed more often in stroke patients. Here, we describe patients in a tertiary teaching hospital in Brazil, emphasizing the impact of age on outcomes.MethodsA retrospective cohort of patients, with malignant strokes which received a decompressive hemicraniectomy, from paper and electronic medical records,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
0
5
0
2
Order By: Relevance
“…The mean age was 54.6 AE 11.6 years and 64.2% were men. At admission, the median NIHSS was 20 (16)(17)(18)(19)(20)(21)(22)(23)(24) and the median GCS was 12 (10)(11)(12)(13)(14). The right hemisphere was the affected in most cases (60.4%).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The mean age was 54.6 AE 11.6 years and 64.2% were men. At admission, the median NIHSS was 20 (16)(17)(18)(19)(20)(21)(22)(23)(24) and the median GCS was 12 (10)(11)(12)(13)(14). The right hemisphere was the affected in most cases (60.4%).…”
Section: Resultsmentioning
confidence: 97%
“…9 There are limited data about DC and stroke in middleincome countries. In the only study from Brazil that 22 In China, Chen et al described a population of 60 patients, with a 27% mortality rate at 1-year. 23 In a cohort of 31 patients with MMCAI treated with DC, 39% were dead after 1year and 52% had mRS 4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study from Brazil (40) presented a cohort of 60 patients with malignant middle cerebral artery (MCA) infarction who underwent unilateral DC. They showed that mortality was higher (67%) in patients > 60 years, while only 44% of the patients from the younger group (<60 years) had mRS 5–6 at 90 days follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, although the great progress has been made in clinical diagnosis and treatment and related basic research to traumatic brain injury, the mortality and morbidity of it still remain the highest (1). And decompressive craniectomy (DC) is still the main and effective treatment for patients with acute severe craniocerebral injury as it is easy to carry out (2). DC is a surgical procedure in which part of the skull is removed to allow the brain to swell without being squeezed.…”
Section: Introductionmentioning
confidence: 99%